A good match or a quarrel? Value co-creation between complementary manufacturers. Issue 12 (2nd December 2021) - Huo, Lisha; Qian, Zhifeng; Shao, Yunfei; Jin, Yi
ABSTRACT: With the increasing complexity of markets, rather than creating offerings in isolation, more and more firms are pursuing value co-creation as part of ecosystem construction. This requires firms to pay greater attention to the integration of complementary resources. Motivated by practice, we develop three game theory models to explore whether focal firms should cooperate with its complementors. We compare models involving non-cooperation, a vertical cooperation strategy, and a horizontal cooperation strategy, finding that complementary manufacturers may prefer vertical cooperation than non-cooperation when the unit production cost of components is not too high. Furthermore, when the level of complementarity and unit production cost of components is pronounced, horizontal cooperation is the most effective mechanism for complementary manufacturers to realise value co-creation, and is always beneficial to traditional suppliers.